Expression of Toll‐like receptors in nasal epithelium in allergic rhinitis - Renkonen, Jutta (APMIS, 2015)
Toll‐like receptors (TLRs) are important in barrier homeostasis, but their role in airborne allergies is not fully understood. The aim was to evaluate baseline and allergen‐induced expression of TLR proteins in nasal epithelium during allergic rhinitis. Nineteen otherwise healthy non‐smoking volunteers both allergic to birch pollen and non‐allergic controls were enrolled. We took nasal biopsies before and after off‐seasonal intranasal birch pollen or diluent challenge. The expression of epithelial TLR1‐7, TLR9‐10, and MyD88 proteins was immunohistochemically evaluated from the nasal biopsies. The TLR1‐3 and TLR5‐10 mRNAs were observed by RNA‐microarray. Baseline epithelial expression of TLR proteins was wide and identical in controls and atopics. After off‐seasonal intranasal birch pollen challenge, a negative change in the expression score of TLR1 and TLR6 proteins was detected in the atopic group. TLR mRNA expression was not affected by birch pollen challenge. Nasal epithelium seems to express all known TLRs. The mechanisms by which TLR1, and TLR6 proteins could affect pollen allergen transport need further studies.